2008
DOI: 10.1352/0895-8017(2008)113[214:snolac]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Noncomprehension of Language: A Comparison of Fragile X Syndrome and Down Syndrome

Abstract: Signaling noncomprehension of the spoken messages of others was examined for youth with fragile X or Down syndrome in comparison with each other and nonverbal MA-matched typically developing children. A direction-following task was used in which some of the directions were inadequate. Both syndrome groups signaled noncomprehension less often than did the typically developing children. The ability to signal noncomprehension appropriately was related to a measure of receptive vocabulary and syntax. Preliminary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
4
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 50 publications
7
88
4
3
Order By: Relevance
“…In fact, Abbeduto et al (2008) examined the ability of 18 adolescents and young adults with FXS (13 boys, 5 girls; mean CA = 17.58 years) to signal noncomprehension of the spoken messages of others, using a direction-following task in which some of the messages were inadequate because (a) the speaker referred to an unavailable object (Incompatible), (b) the speaker's direction was too nonspecific to indicate which object of several available was the intended object (Ambiguous), or (c) the speaker's direction contained an adjective unknown to the participant (Unfamiliar). Abbeduto et al found that the youth with FXS were less likely to signal noncomprehension of inadequate messages than were younger, nonverbal mental age-matched TD children.…”
Section: Fxsmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, Abbeduto et al (2008) examined the ability of 18 adolescents and young adults with FXS (13 boys, 5 girls; mean CA = 17.58 years) to signal noncomprehension of the spoken messages of others, using a direction-following task in which some of the messages were inadequate because (a) the speaker referred to an unavailable object (Incompatible), (b) the speaker's direction was too nonspecific to indicate which object of several available was the intended object (Ambiguous), or (c) the speaker's direction contained an adjective unknown to the participant (Unfamiliar). Abbeduto et al found that the youth with FXS were less likely to signal noncomprehension of inadequate messages than were younger, nonverbal mental age-matched TD children.…”
Section: Fxsmentioning
confidence: 99%
“…The Abbeduto et al (2008) study, however, suffered from a number of limitations that restrict its clinical utility. In particular, the study had a cross-sectional design, relatively small sample size, and/or a very wide age range of participants.…”
Section: Fxsmentioning
confidence: 99%
See 3 more Smart Citations